Menganalisis Kemampuan Menggenggam pada Anak Usia Dini di TK Negeri Pembina Kecamatan Kota Tengah - Indawati Pakaya; Nia Abdullah; Al Melia Putri Kuku; Sulastri Libunelo; Anissa Fahmi Manassai; Sri Yulan Umar (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to analyze the gripping ability of early childhood children at TK Negeri Pembina in Kota Tengah District. The research method used is descriptive with both quantitative and qualitative approaches. The subjects of the study were 10 children aged 4-6 years selected through purposive sampling. Data were collected through direct observation, gripping ability tests, and interviews with teachers. The results show that the gripping ability of children at TK Negeri Pembina varies, with some children able to grip writing tools and small objects well, while others struggle. Factors influencing this ability include stimulation from teachers, interaction with peers, and the activities conducted at school. This study provides insights into the importance of appropriate stimulation and activity variation to enhance children’s fine motor skills